Complexities of Molecular Identification of Î³-herpesviruses: Lessons from MCFV - Turin, Lauretta; Laura Bianchessi (Journal of Advanced Veterinary Research, 2023)
The Herpesviridae family is subdivided into three subfamilies, namely Î±-herpersvirinae, Î²-herpesvirinae and Î³-herpesvirinae. All members of the family are characterized by a common structure consisting of a large linear double-stranded DNA genetic core packaged into a proteic icosahedral capsid and further enclosed in a phospholipidic bilayer envelope of cellular origin. Herpesviruses are characterized, on one side, by a high stability of the genome during virus replication, however, on the other side by a high capability to change rapidly in response to natural evolutionary selecting pressure. Therefore, there is a continuous emergence and establishment of new viruses. In this contest Î³-herpesviruses, whose contribution to disease outbreaks in wildlife population has often been underestimated, pose a serious problem due to their ability to cross species barriers, infect new hosts and give rise to newly emerged viruses or virus variants in reservoirs. The problem is exacerbated by the absence of vaccines and effective treatments, such as for Malignant Catarrhal Fever (MCF) in cattle or MCF-like diseases, caused by the Malignant Catarrhal Fever Viruses (MCFVs). MCFV can infect both livestock and wild animals sporadically, however when it does, it can cause clinical disease with important welfare implications, dramatic pathological changes and often has death as outcome. Due to the inability to isolate the majority of the Î³-herpesviruses in vitro, their detection and characterization necessarily involve molecular methodologies aimed at diagnosing, identifying and resolving their phylogenetic origins and the evolutionary relationship with the host species. This information is ultimately necessary to improve the control of the disease spread, and to better identify the source of outbreaks, which can be seriously detrimental to zoological collections, especially for endangered species. This review provides an overview of the currently available methodologies applied for identification and characterization of MCFVs, critically describes benefits and disadvantages of these, recognises the gaps to be addressed and identifies future diagnostic opportunities.